Orbital Shift‐Induced Boundary Obstructed Topological Materials with a Large Energy Gap. Issue 27 (29th July 2022) - Mao, Ning; Li, Runhan; Dai, Ying; Huang, Baibiao; Yan, Binghai; Niu, Chengwang
Abstract: Boundary obstructed topological phases caused by Wannier orbital shift between ordinary atomic sites are proposed, which, however, cannot be indicated by symmetry eigenvalues at high symmetry momenta (symmetry indicators) in bulk. On the open boundary, Wannier charge centers can shift to different atoms from those in bulk, leading to in‐gap surface states, higher‐order hinge states or corner states. To demonstrate such orbital shift‐induced boundary obstructed topological insulators, eight material candidates are predicted, all of which are overlooked in the present topological databases. Metallic surface states, hinge states, or corner states cover the large bulk energy gap (e.g., more than 1 eV in TlGaTe2 ) at related boundary, which are ready for experimental detection. Additionally, these materials are also fragile topological insulators with hourglass‐like surface states. Abstract : The authors put forward t he boundary obstructed topological phases caused by Wannier orbital shift between ordinary atomic sites. Moreover, a general principle to trigger the higher‐order states is proposed. Armed with this method, five material candidates are predicted for second‐order and three for third‐order topological insulators, all of which are overlooked in the present topological databases.